DIMENSI PENDIDIKAN SHALAT BAGI MANUSIA (Kajian Kritis terhadap Tasyri’ Shalat) - Said, Ali (Al Tadib : Jurnal Ilmu Pendidikan, 2016)
This article intends to examine the educational dimension of shalat for humans. Through the concept offered by law, prayer is not only a means of ritual expression of a servant to worship God, let alone just a religious duty that must be met by all adherents without understanding the function and mission execution of such obligations. Shalat is the lessons learned from the discipline of the time, speech, movement, concentration, and packed full compliance in the theme of prayer which include; cognitive, affective and psychomotor. Therefore to understand prayer as a whole, then the prayer is, and must also be understood for whom prescribed prayers, which in turn indicates that the recipes offered through prayer will be able to understand and be understood, this understanding will realize the importance of prayer actors for him, and in the end the prayer performed with high awareness, without compulsion. If everything was done voluntarily and happily, then comfort will arise, naturally, instinctively, people who feel comfortable life then certainly it would be a good person, a good person will always do things that are good also. Changed and these changes are an indication of the success of obliged praying for humans. Humans who received correctly and continuously every day five times a person will definitely be righteous, namely, ashshaalihiin that according to Quran is a group of people who are devoted to God and who joined the group of prophets, people who always true, and the martyrs. Keywords: Education prayer, shalat